Tensions of The Tension of Sectarianism and the Challenges of Democracy in the Middle East After Arab Spring - Sainul Rahman (Indonesia Center for Middle East Studies, 2019)
The Arab Spring wave in early 2011 that hit Middle East countries, starting from Tunisia, Egypt, Libya, Bahrain, Kuwait, Saudi Arabia, Yemen, and Syria showed the will of the Arab people to achieve improvements in various fields, ranging from economic, social, to an open and democratic political system. After eights years since it started, several countries are still continuing the process of democratization, such as Tunisia and Egypt. On the other hand, in some countries, the democratization process has stalled, such as in Saudi Arabia, Bahrain, and Kuwait, and there are countries that have fallen in prolonged war, namely Libya, Yemen, and Syria. This article discusses two case studies to see how sectarianism occured after the Arab Spring, namely Tunisia and Yemen. Using a historical approach with descriptive analysis, the authors found that although sectarianism in the Middle East has a long historical root, in the Arab Spring conflicts sectarianism has been used by parties in conflict to achieve their respective interests. As long as the conflicting parties continue using political identity and sectarianism, it is difficult to achieve an established democracy.